Discovery of anti-SARS-CoV-2 S2 protein antibody CV804 with broad-spectrum reactivity with various beta coronaviruses and analysis of its pharmacological properties in vitro and in vivo. - Yoji Tsugawa; Kentaro Furukawa; Tomoko Ise; Masahiro Takayama; Takeshi Ota; Takayuki Kuroda; Shinya Shano; Takashi Hashimoto; Haruyo Konishi; Takeshi Ishihara; Masaaki Sato; Haruhiko Kamada; et al. (PLoS ONE)
The SARS-CoV-2 pandemic alerted the potential for significant harm due to future cross-species transmission of various animal coronaviruses to human. There is a significant need of antibody-based drugs to treat patients infected with previously unseen coronaviruses. In this study, we generated CV804, an antibody that binds to the S2 domain of SARS-CoV-2 spike protein, which is highly conserved across the coronavirus family and less susceptible to mutations. CV804 demonstrated broad cross-reactivities not only disease-associated human beta coronaviruses including SARS-CoV, MERS-CoV, HCoV-OC43, HCoV-HKU1 and with existing mutant strains of SARS-CoV-2 and but also with 20 representative animal-origin coronaviruses. CV804 exhibits strong antibody-dependent cellular cytotoxicity (ADCC) to SARS-CoV-2 spike protein expressed on cells in vitro, while completely lacks virus-neutralization activity. In animal models, CV804 suppressed disease progression caused by SARS-CoV-2 infection. Structural studies using HDX-MS combined with reactivity analysis with point mutants of recombinant spike proteins revealed that CV804 binds to a unique conformational epitope within the S2 domain of the spike proteins that is highly conserved among various coronaviruses. Overall, obtained data suggest that the non-neutralizing CV804 antibody recognizes the conformational structure of the spike protein displayed on the surface of infected cells and weakens the viral virulence by supporting the host immune cells' attack through ADCC activity in vivo. The CV804 epitope information revealed in this study is useful for designing pan-corona antibody therapeutics and universal coronavirus vaccines for preparing potential future pandemics.